Reducing Public Poverty Through Optimization of Zakat Funding as an Effort to Achieve Sustainable Development Goals (SDGs) in Indonesia - Syamsuri Syamsuri; Yaumi Sa’adah; Isma Aulia Roslan (Jurnal Ilmiah Ekonomi Islam, 2022)
Optimization of zakat is an urgent thing to do to overcome the Muslim community in Indonesia from the poverty line. Poverty in Indonesia is an important problem to find a solution. For some time, the poverty rate in Indonesia is said to have not been stable. According to data from the Central Statistics Agency, the poverty rate in Indonesia as of March 2021 reached 27.54 million people, which amounted to 10.14 percent of the total national population. The use of zakat is one of the instruments to provide development solutions and equalize the economy. The government is also pursuing the same goal through sustainable development programs (SDGs). This research method is a qualitative research using a literature approach. What is used in this research is a literature study, which is a type of research whose data is obtained from books, books, magazines, newspapers, journals and other records that have relevance to the problems to be discussed. The results of this study are the role of zakat has been proven to provide an alternative for reducing poverty for the community, especially Muslims in Indonesia. Zakat can help the government to eradicate poverty. One of the efforts that can be made by the Amil Zakat Institution is the process of changing service recipients from mustahik to muzakki through an empowerment process. Thus zakat funds can change a person's life without dependence. The relationship between zakat management and the achievement of the SDGs, is an idea where an approach that is on the belief system/spirituality of the community will be accepted by the community with their values and beliefs. Actually Zakat can be a source of funding in empowerment programs, but it does not stop at that. In zakat itself, there are values that can be developed that can answer the process of achieving the SDGs targets. Keywords: Zakat, Sustainable Development Goals (SDGs), Poverty.